A review of polymeric composite membranes for gas separation and energy production - Liang, Can Zeng; Chung, Tai-Shung; Lai, Juin-Yih (Progress in polymer science, 2019)
[Display omitted] Membrane-based technologies for gas and vapor separations have been industrialized for more than three decades due to (1) the invention of asymmetric composite membranes and (2) their superior energy-efficient and environment-friendly characteristics. However, industries demand more robust and productive composite membranes to meet the harsh conditions in new or emerging applications. The fabrication of thin film composite (TFC) membranes consisting of an ultrathin selective layer and a strong porous substrate will likely play the pivotal role to meet the future demands. In this review, we revisit the basis of composite membranes for gas and vapor separations with the aim to produce next-generation high-performance composite membranes. This review focuses on (1) the fundamentals of gas transport theories through composite membranes, (2) fabrication techniques, and (3) performance characteristics and stability of composite membranes. We examine, elucidate and explore the state-of-the-art techniques for the fabrication of composite membranes. Based on the resistance model, we derive a new generalized equation for gas permeance, which is simple, informative and applicable to composite membranes. We also outline the directions, challenges and key areas for future R&D in the field of gas/vapor-separation composite membranes.